Penentuan Strategi CRM Pada Segmentasi Customer Lifetime Value Menggunakan Model LRFMV dan Metode K-Medoids - Erika Fernanda Ardanariswari (Fakultas Ilmu Komputer, 2023)
This research aims to segment customers based on sales transaction data at Orange Mart. This research uses the LRFMV model and the K-Medoids clustering method to calculate the CLV value in each cluster which will later form a CRM strategy. To determine the optimal number of clusters in this study, the Elbow method was used which resulted in 2 clusters. The highest CLV value is generated by cluster 0, namely 0.216676888, and the lowest value is obtained by cluster 0, namely 0.105924241. So that the CRM strategy formed in each cluster is in cluster 0, namely by maintaining communication with customers and forming special programs for customers in this segment, while in cluster 1, namely conducting customer satisfaction surveys to retain customers.
Reuploud Repository hasyim Mei 2026 :: Finalisasi Repositori File 4 Juni 2026_Kurnadi
Keywords: Customer Segmentation; K-Medoids; Elbow; CRM; CLV